Efficient photodynamic therapy against gram-positive and gram-negative bacteria using THPTS, a cationic photosensitizer excited by infrared wavelength. - Stanislaw Schastak (Public Library of Science (PLoS), 2010)
The worldwide rise in the rates of antibiotic resistance of bacteria underlines the need for alternative antibacterial agents. A promising approach to kill antibiotic-resistant bacteria uses light in combination with a photosensitizer to induce a phototoxic reaction. Concentrations of 1, 10 and 100microM of tetrahydroporphyrin-tetratosylat (THPTS) and different incubation times (30, 90 and 180min) were used to measure photodynamic efficiency against two Gram-positive strains of S.aureus (MSSA and MRSA), and two Gram-negative strains of E.coli and P.aeruginosa. We found that phototoxicity of the drug is independent of the antibiotic resistance pattern when incubated in PBS for the investigated strains. Also, an incubation with 100microM THPTS followed by illumination, yielded a 6lg (> or =99.999%) decrease in the viable numbers of all bacteria strains tested, indicating that the THPTS drug has a high degree of photodynamic inactivation. We then modulated incubation time, photosensitizer concentration and monitored the effect of serum on the THPTS activity. In doing so, we established the conditions to obtain the strongest bactericidal effect. Our results suggest that this new and highly pure synthetic compound should improve the efficiency of photodynamic therapy against multiresistant bacteria and has a significant potential for clinical applications in the treatment of nosocomial infections.